PENGARUH PENGEMBANGAN KARIR, DISIPLIN KERJA DAN KOMITMEN ORGANISASI TERHADAP KINERJA PEGAWAI KANTOR CAMAT MANGGIS, KABUPATEN KARANGASEM - I Made Agus Budiana; Nengah Landra; Ni Made Dwi Puspitawati (Program Studi Manajemen Fakultas Ekonomi dan Bisnis UNMAS, 2021)
The purpose of this study was to determine the effect of career development, work discipline, and organizational commitment on employee performance. This research was conducted at Manggis District Office of Karangasem Regency.This study uses multiple linear regression analysis to determine the effect of career development, work discipline, and organizational commitment on employee performance at Manggis District Office of Karangasem Regency. Data were collected by distributing questionnaires and the sampling method used was the census method. Testing the research hypothesis using SPSS 21.0 for Windows. The results showed that (1) career development partially had a positive and significant effect on employee performance (2) work discipline partially has a positive and significant effect on employee performance (3) organizational commitment partially has a positive and significant effect on employee performance. Based on the results of these studies, leaders need to make policies concerning the improvement of career development, work discipline, and organizational commitment to optimize employee performance.